Um framework para sistemas baseados em conhecimento no contexto da metodologia CommonKADS - Marchi, Gécen Dacome De (2010)
In addition to requiring the use of methodologies, techniques and tools for building knowledge systems, as in the development of any kind of software should be considered the complexity of these systems and high dependence on domain experts. The complexity ranges from the acquisition of knowledge and explanation to its representation and distribution. To make the process of developing systems for more systematic knowledge, there are specific methodologies, CommonKADS is the best known and currently used, and to expedite this process can be used as frameworks that have goals and achieving reuse of software with high cohesion and loosely. These characteristics are desired by the engineers and software developers, especially by facilitating maintenance. The high dependence on domain experts during the development and use of systems of knowledge leads to greater demand for communication both among developers and experts such as between the latter and the system. Communication between developers and domain experts can be facilitated with the construction of models of the CommonKADS methodology, which are used for knowledge representation and general characteristics of the system being implemented. To increase the availability of knowledge and facilitate their communication with domain experts and other users, you can use web services. In this context, this paper presents a Framewok developed according to the CommonKADS design methodology, where the main concern is the manner of acquisition and knowledge representation. This framework, as well as facilitate the construction of knowledge systems, enables these systems are available as web services.